Penggunaan Media Awetan pada Materi Jamur untuk Meningkatkan Ketuntasan Belajar Siswa Kelas X-1 SMA Negeri 1 Sekaran - LINDA NOVITASARI (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
This research aim was to (1) discover the appropriateness of student worksheet which is developed in observation activities; (2) analyze the concept understanding which is used to reach learning outcomes; (3) describe student activity; and (4) describe students’ and teacher’s response towards the observation activities. Type of research is applied research using one-shot case study. The result showed that the developed worksheet was appropriate to be used in field by score of 85, 71%. The classical learning outcomes was 91% and performed by 31 students. Student’s activities were categorized very well for each aspect by score 3,00. Teacher’s and students’ response towards the observation activities was also positive. Keywords- fungal wet-preserved media, observation, learning outcomes